2010
DOI: 10.1111/j.1445-2197.2010.05584.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone flap storage following craniectomy: a survey of practices in major Australian Neurosurgical centres

Abstract: This study has documented highly varied skull flap cryopreservation and storage practices in neurosurgical centres throughout Australia. These differences may contribute to relatively high complication rates of infection and bone resorption reported in the literature. The results of the current study argue for the further need of high quality clinical and basic science research, which aims to characterize the effect of current skull flap management practices and freeze-storage conditions on the biological and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…[71016] Current practices relating to cranioplasties are subjective and based either on the surgeon's preferences or institutional policies and there is a void of literature on practices that can potentially minimize the risk of complications. [322]…”
Section: Discussionmentioning
confidence: 99%
“…[71016] Current practices relating to cranioplasties are subjective and based either on the surgeon's preferences or institutional policies and there is a void of literature on practices that can potentially minimize the risk of complications. [322]…”
Section: Discussionmentioning
confidence: 99%
“…Bhaskar et al reported that all 25 major Australian neurosurgical institutions surveyed utilized this storage method. 22 Importantly, this study further highlighted the significant variations in techniques and physical conditions (for example, À18°C to À83°C). Similar variations have also been reported elsewhere although the optimal conditions of skull bone storage are not known.…”
Section: Discussionmentioning
confidence: 96%
“…However, there is not a lot of information on how to cryopreserve skull flaps. Bhaskar et al8) reported 96% of 25 neurosurgical centers in Australia used cryopreserved autologous bone flaps for cranioplasty. In his report, 88% of institutions used double or triple gabbed under dry, sterile conditions for packing bone flaps.…”
Section: Autologous Skull Flapmentioning
confidence: 99%
“…In his report, 88% of institutions used double or triple gabbed under dry, sterile conditions for packing bone flaps. The bone flaps were cryopreserved at temperatures between -18℃ and -83℃ 8). Biomechanical studies reveal that freezing and thawing have little effect on the mechanical properties of the human skull 54).…”
Section: Autologous Skull Flapmentioning
confidence: 99%
See 1 more Smart Citation